Impact of educational intervention on knowledge of dispensers working at community pharmacies in Pakistan - Hussain A; Ibrahim MI; Malik M (Centro de Investigaciones y Publicaciones Farmaceuticas, 2013)
Objective: To evaluate the impact of training of dispensers on knowledge of dispensers working at community pharmacies in context to storage temperature, prescription terminologies and status of medicines in Islamabad, Pakistan.Method: A randomized, controlled, blinded intervention study was designed and implemented. Before the implementation of intervention, a baseline study was performed to assess the knowledge of dispensers working at community pharmacies. The study population included all community pharmacy outlets in Islamabad. Pharmacies of Islamabad which were visited in pre intervention phase (n=118) were divided into two geographical regions: A (intervention) and B (control). Thirty pharmacies were randomly selected from each region. Keeping in view the results of the baseline study an educational intervention was designed to improve the knowledge of dispensers working at community pharmacies in Pakistan.Results: A significant difference in the overall knowledge of dispensers was observed between the pre-post intervention groups. Knowledge of dispensers regarding storage of drugs, prescription terminologies and status of drugs was improved after the training. On the other hand no significant difference was observed between the pre-post control groups.Conclusion: The study has highlighted that improvements in knowledge of dispensers working at community pharmacies are possible through suitable interventions. But, results of interventions can only be sustainable through continuous monitoring and reinforcement of the training.